Aqua crop model-based simulation of supplemental irrigation effect on Haricot bean (Phaseolus vulgaris L.) yield and water productivity in moisture stress areas of Southern Ethiopia - Gezimu Gelu Otoro; Samuel Dagalo Hatiye (Discover Agriculture)
Abstract Supplemental irrigation (SI) is crucial for enhancing the productivity of crops, including Haricot beans (Phaseolus vulgaris L.), in regions with limited rainfall, including the semiarid region of southern Ethiopia. This study evaluated the effects of supplemental irrigation (SI) applied at different growth stages on yield, biomass, and water productivity (WP) over three years (2020-2022) via six treatments: T1 (rainfed), T2 (SI throughout growing seasons), T3 (SI at the vegetative, flowering, and pod formation stages), T4 (SI at the vegetative and pod formation stages), T5 (SI at the emergence, flowering, and grain filling stages), and T6 (SI at the emergence, pod formation, and grain filling stages). The full SI treatment (T2) yielded the highest yield, whereas T3 and T4 presented statistically non siginificant yields and biomasses, indicating moisture stress tolerance during emergence and late maturity. The study was carried out using a complete random block design (RCBD) with three replications. The statistical analysis revealed that T3 achieved the highest WP, followed by T4, which showed a greater WP than did the full SI. The Aqua crop model performance metrics also revealed that the model-simulated and field-observed parametric values strongly correlated with biomass, Wp and yield across years (2020–2022). The current findings reveal that implementing SI during critical growth stages (T3 or T4) maximizes yield and WP while saving water in water scarce region. Further investigation should focus on simulating water productivity, yield, and economic gains, taking into account diseases, climatic variables and water quality parameters..